A New Immunological Prognostic Model Based on Immunohistochemistry for Extranodal Natural Killer/T-Cell Lymphoma Patients After Non-Anthracycline-Based Chemotherapy - Lam ST; Huang H; Fang X; Wang Z; Hong H; Ren Q; Tian Y; Lin S; Lin T (Cancer Management and Research, 2020)
Sio Teng Lam,1,2,* He Huang,1,* Xiaojie Fang,1 Zhao Wang,1 Huangming Hong,3 Quanguang Ren,1 Ying Tian,1 Suxia Lin,4 Tongyu Lin1 1Department of Medical Oncology, Sun Yat-Sen University Cancer Center, State Key Laboratory of Oncology in Southern China, and Collaborative Innovation Center of Cancer Medicine, Guangzhou, People’s Republic of China; 2Department of Medical Oncology, Centro Hospitalar Conde De Sao Januario, Macau, People’s Republic of China; 3Department of Medical Oncology, Sun Yat-Sen Memorial Hospital, Sun Yat-Sen University, Guangzhou, People’s Republic of China; 4Department of Pathology, Sun Yat-Sen University Cancer Center, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tongyu LinDepartment of Medical Oncology, Sun Yat-Sen University Cancer Center, State Key Laboratory of Oncology in Southern China, and Collaborative Innovation Center of Cancer Medicine, 651 Dongfeng Road East, Guangzhou, Guangdong 510060, People’s Republic of ChinaTel +86-20-87343363Fax +86-20-87343294Email tongyulin@hotmail.comPurpose: Programmed death ligand 1 (PD-L1) has been proposed as an important prognostic factor in many types of cancer. However, the role of predicting the prognosis of PD-L1 in extranodal natural killer/T-cell lymphoma (ENKTL) was controversial. Combining other biomarkers might enhance its predictive power. This study aims to evaluate the prognostic value of PD-L1 in conjunction with tumor-infiltrating FoxP3+Tregs for ENKTL after non-anthracycline-based chemotherapy.Patients and Methods: A total of 81 patients with ENKTL were included in this study. Clinicopathological characteristics were collected, and prognostic significance of PD-L1 in neoplastic cells (nPD-L1) and tumor-infiltrating FoxP3+Tregs were evaluated.Results: Patients with nPD-L1-positive had significantly inferior overall survival (OS) and progression-free survival (PFS) compared with nPD-L1-negative (3-year OS, 37.2% vs 67.3%, p = 0.014; 3-year PFS, 31.0% vs 61.8%, p =0.010, respectively). Patients who had low FoxP3+Tregs had significantly inferior OS and PFS compared with high FoxP3+Tregs (3-year OS, 36.4% vs 63.0%, p = 0.004; 3-year PFS, 31.7% vs 56.3%, p = 0.020, respectively). The results of multivariate analysis showed that nPD-L1 positivity (HR 6.629, 95% CI 1.966– 22.350, p=0.002) and low FoxP3+Tregs (HR 7.317, 95% CI 2.154– 24.855, p=0.001) were independent predictors of inferior OS. Using these 2 variables, we constructed a new prognostic model that singled out 3 groups with different risk profiles: group 1, no adverse factors; group 2, 1 adverse factor; and group 3, 2 adverse factors. The 3-year OS rates of group 1, group 2, and group 3 were 93.3%, 46.6% and 20.8%, respectively (p< 0.001), and the 3-year PFS rates were 86.7%, 40.8% and 15.0%, respectively (p=0.001).Conclusion: This study is the first to validate the prognostic value of nPD-L1 and tumor-infiltrating FoxP3+Tregs in ENKTL; the new immunological prognostic model might be used to stratify ENKTL patients in clinical trials for new therapeutic strategies.Keywords: extranodal natural killer/T-cell lymphoma, PD-L1, FoxP3+Tregs, prognosis